2017
DOI: 10.2217/pgs-2017-0091
|View full text |Cite
|
Sign up to set email alerts
|

Prior Opioid Exposure Influences Parents’ Sharing of Their Children’s CYP2D6 Research Results

Abstract: Prior opioid exposure influenced perceived clinical utility and sharing behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…A previous case/control study found that parents of children exposed to opioids were more likely to share the child’s CYP2D6 results with their primary care provider as compared to children not exposed to opioids, and believed their child’s doctor could use that information for improved care. 19 Additionally, the disease state that is being treated may influence the likelihood or the extent to which parents or individuals pursue PGx testing. Diagnoses such as attention deficit hyperactivity disorder, which can be challenging for the parent, patient, and provider, have PGx panels specifically marketed by companies for this disease state.…”
Section: Relationship Between the Medxp And Pgxmentioning
confidence: 99%
“…A previous case/control study found that parents of children exposed to opioids were more likely to share the child’s CYP2D6 results with their primary care provider as compared to children not exposed to opioids, and believed their child’s doctor could use that information for improved care. 19 Additionally, the disease state that is being treated may influence the likelihood or the extent to which parents or individuals pursue PGx testing. Diagnoses such as attention deficit hyperactivity disorder, which can be challenging for the parent, patient, and provider, have PGx panels specifically marketed by companies for this disease state.…”
Section: Relationship Between the Medxp And Pgxmentioning
confidence: 99%